The novel compound Sul-121 preserves endothelial function and inhibits progression of kidney damage in type 2 Diabetes Mellitus in mice - Lambooy, Suzanne; Wiedenmann, Tanja (Scientific reports, 2017)
Diabetic nephropathy is still a common complication of type 2 diabetes mellitus (T2DM) and improvement of endothelial dysfunction (ED) and inhibition of reactive oxygen species (ROS) are considered important targets for new therapies. Recently, we developed a new class of compounds (Sul compounds) which inhibit mitochondrial ROS production. Here, we tested the therapeutic effects of Sul-121 on ED and kidney damage in experimental T2DM. Diabetic db/db and lean mice were implanted with osmotic pumps delivering Sul-121 (2.2 mg/kg/day) or vehicle from age 10 to 18 weeks. Albuminuria, blood pressure, endothelial mediated relaxation, renal histology, plasma creatinine, and H2O2 levels were assessed. Sul-121 prevented progression of albuminuria and attenuated kidney damage in db/db, as evidenced by lower glomerular fibronectin expression (~50%), decreased focal glomerular sclerosis score (~40%) and normalization of glomerular size and kidney weight. Further, Sul-121 restored endothelium mediated vasorelaxation through increased production of Nitric Oxide production and normalized plasma H2O2 levels. Sul-121 treatment in lean mice demonstrated no observable major side-effects, indicating that Sul-121 is well tolerated. Our data show that Sul-121 inhibits progression of diabetic kidney damage via a mechanism that involves restoration of endothelial function and attenuation of oxidative stress.